Clinical outcomes of closed reduction vs. small-incision-assisted open reduction with intramedullary nailing in complex comminuted femoral shaft fractures (AO/OTA 32-C): a retrospective cohort study - Li, Qingwei; Wang, Jianqiang; Sun, Chunyan; Lu, Lintao; Mu, Zongyou; Zhang, Xubin (Frontiers in Surgery, 2025)
BackgroundIntramedullary nailing (IMN) is the preferred treatment owing to its minimally invasive nature, high healing rates, and reduced stress shielding. However, the optimal reduction method for complex comminuted fractures (AO/OTA 32-C) has been controversial. Closed reduction preserves blood supply but requires extensive fluoroscopy and technical expertise. Small-incision-assisted open reduction enhances visualisation and facilitates reduction but entails slightly increased soft tissue exposure.MethodsThis retrospective cohort study analysed 70 patients with AO/OTA 32-C femoral shaft fractures treated with intramedullary nailing. Patients were categorised into a Closed reduction group (n = 35) and Small-incision-assisted open reduction group (n = 35). Outcomes assessed included operative time, fluoroscopy usage, blood loss, infection rates, hospital stay duration, and functional outcomes at 3, 6, and 12 months postoperatively.ResultsThe Small-incision-assisted open reduction group had shorter operative times (45.09 ± 5.67 vs. 78.34 ± 5.71 min, P < 0.05) and lower fluoroscopy usage (6.03 ± 1.51 vs. 22.33 ± 5.99, P < 0.05). While blood loss and incision length were higher, infection rates and hospital stays were comparable between the groups. Functional outcomes at 3 and 6 months were significantly better in the Small-incision-assisted open reduction group, with no differences at 12 months. The Small-incision-assisted open reduction group also had a higher excellent-to-good fracture healing rate (88.6% vs. 60.0%, P < 0.05).ConclusionsSmall-incision-assisted open reduction reduces operative time, fluoroscopy usage, and improves early functional outcomes. It is a safe and efficient alternative to closed reduction, but larger multi-centre studies are needed for broader validation.